Postpartum Depression in Mothers of Infants with Very Low Birth Weight - Khan, Misbah; Naseeb, Shazia (Biological and Clinical Sciences Research Journal, 2025)
Postpartum depression (PPD) remains a significant public health concern, particularly among mothers of infants with very low birth weight (VLBW). Despite advancements in neonatal intensive care improving survival outcomes, maternal psychological health is often overlooked. The present study explores the association between infant birth weight and maternal depression severity. Methods: A cross-sectional analytical study was conducted at Ward 8 of Jinnah Postgraduate Medical Centre, Karachi, from January 2024 to January 2025. A total of 110 postpartum mothers were recruited using non-probability sampling. The participants were categorized into two groups: mothers of infants with birth weights <2500g and ≥2500g. Data were collected using a structured questionnaire comprising demographic details and the Edinburgh Postnatal Depression Scale (EPDS). Statistical analyses included Pearson correlation, chi-square test, and multinomial logistic regression using SPSS version 17.0. Results: The mean EPDS scores were significantly higher among mothers of infants with birth weight <2500g (16.29±3.14) compared to those with normal birth weight (13.38±2.78) (p<0.001). Regression analysis indicated a strong association between low birth weight and elevated PPD risk, even after controlling for confounders such as maternal age, education, parity, and family support. Additionally, unplanned pregnancies, cesarean deliveries, and longer neonatal intensive care unit (NICU) stays were linked to higher depression scores. Conclusion: Very low birth weight is a significant predictor of postpartum depression. Early identification of high-risk mothers, especially those with limited family support and VLBW infants, is crucial. Routine psychological screening and integrated postpartum care are recommended to mitigate adverse maternal and infant outcomes.